Self-Critical and Self-Punishment Cognitions Differentiate Those With and Without a History of Nonsuicidal Self-Injury: An Ecological Momentary Assessment Study. Issue 3 (May 2021) - Burke, Taylor A.; Fox, Kathryn; Kautz, Marin M.; Rodriguez-Seijas, Craig; Bettis, Alexandra H.; Alloy, Lauren B.
Abstract : The aim of this study was to examine trait, state, and temporal instability measures of self-critical and self-punishment cognitions to evaluate their respective roles in nonsuicidal self-injury (NSSI). Participants were university students with a history of NSSI ( n = 64) and those with no history of NSSI ( n = 59). At baseline, participants completed measures assessing history of NSSI behavior, as well as trait measures of self-criticism and self-punishment. After completion of baseline procedures, participants subsequently participated in a 10-day ecological momentary assessment protocol in which self-critical and self-punishment cognitions were assessed in real time three times daily. Employing bivariate and multivariate frameworks, our results demonstrate that both trait and state levels of self-critical and self-punishment cognitions robustly differentiate between young adults with and without a lifetime history of NSSI. The present results also confirm that the temporal instability of these cognitive states also meaningfully differentiate between groups, such that those who exhibit greater fluctuations in these cognitive states are more likely to have a history of NSSI. The current findings suggest that trait, state, and temporal instability of negative self-focused cognitions may be vulnerability factors for engagement in NSSI. Highlights: Trait self-criticism and self-punishment cognitions are associated with past NSSI State self-critical and self-punishment cognitions are associated with past NSSI Multilevel confirmatory factor analysis confirms state-level associations with NSSI Temporal instability of these cognitions are associated with past NSSI